2016
DOI: 10.1016/j.jhazmat.2016.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Characterising legacy spent nuclear fuel pond materials using microfocus X-ray absorption spectroscopy

Abstract: Analysis of a radioactive, coated concrete core from the decommissioned, spent nuclear fuel cooling pond at the Hunterston-A nuclear site (UK) has provided a unique opportunity to study radionuclides within a real-world system. The core, obtained from a dividing wall and sampled at the fill level of the pond, exhibited radioactivity (dominantly (137)Cs and (90)Sr) heterogeneously distributed across both painted faces. Chemical analysis of the core was undertaken using microfocus spectroscopy at Diamond Light S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…17,20 Sr complexes strongly with metal oxides (e.g. TiO2, FeOOH, Fe3O4) [21][22][23][24][25] through surface complexation reactions, and with clay minerals (e.g., talc, 17 illite, illite-smectite mixed layered phases, [25][26][27] bentonite, 28 and kaolinite 24,29 ) through both surface complexation and cation exchange reactions. 17,28,30 Cs interacts strongly with clay minerals through cation exchange reactions 17,26,31,32 and through surface complexation on the basal surface of clay minerals.…”
Section: Introductionmentioning
confidence: 99%
“…17,20 Sr complexes strongly with metal oxides (e.g. TiO2, FeOOH, Fe3O4) [21][22][23][24][25] through surface complexation reactions, and with clay minerals (e.g., talc, 17 illite, illite-smectite mixed layered phases, [25][26][27] bentonite, 28 and kaolinite 24,29 ) through both surface complexation and cation exchange reactions. 17,28,30 Cs interacts strongly with clay minerals through cation exchange reactions 17,26,31,32 and through surface complexation on the basal surface of clay minerals.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that radioactive material can be deposited on the surfaces of nuclear facility infrastructure leading to regions of contamination. The presence of radioactive contamination on steel surfaces has numerous repercussions for the nuclear industry as a significant amount of stainless steel is used across the nuclear estate. In the UK alone, there is approximately 32 000 tonnes of contaminated stainless steel that is classified as intermediate level waste (ILW) .…”
Section: Introductionmentioning
confidence: 99%
“…24,26 Sr has been identified to complex with titanium dioxide (common as an accessory mineral in clayey soils 3,4 ) through forming inner-sphere surface complexes with anatase and rutile. 27,28 Cs complexes strongly with clay minerals such as illite and smecitite; 29,30 however, identifying Cs complexation mechanisms with clay minerals is more challenging compared to Sr due to the limitations with respect to Cs X-ray absorption spectroscopy. 19,31 Various studies have proposed the formation of outer-sphere surface complexes with clay minerals 24,[32][33][34] at relatively high concentrations.…”
Section: Introductionmentioning
confidence: 99%